STRAWBERRY GENERATION COMMUNICATION TRANSFORMATION "OFFLINE AND ONLINE" - adrian, donal; Siahaan, Chontina (Jurnal Paradigma, 2024)
Generally, the strawberry generation such as students prefer to mention negative words when communicating with other people's friends. The aim of this research is to find out the transformation of strawberry generation communication both offline and online. Qualitative research method with purposive informant retrieval technique. Data collection techniques are in-depth interviewing and direct observation. For analysis techniques using Data Reduction, Data Display, and Conlusion Drawing / Verification. The results showed that the strawberry generation's communication transformations such as students tend to be latent by showing negative words that are considered cool such as anjay, anjir, bjir, crazy, and others. The message is intended to call someone, praise certain things, and get angry at a situation. This is used to show self-existence that they can adapt to the sentences that many other people use on social media and direct communication. Furthermore, other behavioral transformations shown by the strawberry generation such as students are related to the lifestyle of vacationing, culinary, make-up, listening to music, having gadgets, fashion, and gathering in a place such as a cafe just to spend time with less communication intensity because they use more social media on smartphones. The activities carried out are then uploaded on social media accounts as a form of self-existence in the hope of getting praise or just replying to comments from netizens.